Physical exercise in amyotrophic lateral sclerosis: a potential co-adjuvant therapeutic option to counteract disease progression - Fenili, Gianmarco; Scaricamazza, Silvia; Ferri, Alberto; Valle, Cristiana; Paronetto, Maria Paola (Frontiers in Cell and Developmental Biology, 2024)
Amyotrophic lateral sclerosis (ALS) is a fatal disorder characterized by the selective degeneration of upper and lower motor neurons, leading to progressive muscle weakness and atrophy. The mean survival time is two to five years. Although the hunt for drugs has greatly advanced over the past decade, no cure is available for ALS yet. The role of intense physical activity in the etiology of ALS has been debated for several decades without reaching a clear conclusion. The benefits of organized physical activity on fitness and mental health have been widely described. Indeed, by acting on specific mechanisms, physical activity can influence the physiology of several chronic conditions. It was shown to improve skeletal muscle metabolism and regeneration, neurogenesis, mitochondrial biogenesis, and antioxidant defense. Interestingly, all these pathways are involved in ALS pathology. This review will provide a broad overview of the effect of different exercise protocols on the onset and progression of ALS, both in humans and in animal models. Furthermore, we will discuss challenges and opportunities to exploit physiological responses of imposed exercise training for therapeutic purposes.